PENOLAKAN RUSIA TERHADAP PEMBANGUNAN TRANS CASPIAN GAS PIPELINES 2006-2014 - Putri Jayantari, Ni Nyoman Diah; Sushanti, Sukma; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2017), 2017)
ABSTRACT The construction of Trans-Caspian gas pipeline, a new promising pipeline in Caspian region triggered Russia’s opposition. The opposition came up as geopolitic importance of the region and the economic interest of Russia will be significantly harmed due to the construction. Based on that idea, this research analyzes the policies that Russia took as an effort to declare it opposition and stop the contruction of the pipeline. Data in this research were collected from various sources including official website, journals, books, news and reports. To analyze, the research used foreign policy concept and rational actor model. The research shows that the policy decided by Russia is the most rational policy that successfully postponed and possibly stopping the contruction of Trans-Caspian Gas Pipeline. Keywords : Energy, Russia, Trans-Caspian Gas Pipeline